2019
DOI: 10.3390/en12010191
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Comprehensive Performance of Hygroscopic Materials in an Office Building Based on EnergyPlus

Abstract: This paper presents the research status of hygroscopic materials, points out the weak links as targets for major breakthroughs, and introduces humidifying mechanisms and their categories. In this paper, we simulated a single-monomer Shenyang office building with different envelopes of inner-surface hygroscopic materials for indoor humidity conditions, energy consumption, and economy, which are three aspects of energy consumption analysis in EnergyPlus software. To obtain the best moisture buffering performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…It is important to highlight that the simulations tools employed in this research are highly recommended by several international and renowned standards, which have been greatly used in several scientific investigations [41][42][43][44][45][46]. Accordingly, the simulation tools accuracy supports the results reliability of the energy efficiency of the building in its original state, without thermal insulation materials, and the results of the energy efficient version, demonstrating thus the effectiveness of the strategies implemented for the climate under analysis.…”
mentioning
confidence: 58%
“…It is important to highlight that the simulations tools employed in this research are highly recommended by several international and renowned standards, which have been greatly used in several scientific investigations [41][42][43][44][45][46]. Accordingly, the simulation tools accuracy supports the results reliability of the energy efficiency of the building in its original state, without thermal insulation materials, and the results of the energy efficient version, demonstrating thus the effectiveness of the strategies implemented for the climate under analysis.…”
mentioning
confidence: 58%
“…In existing studies [41,42], this method had been demonstrated as having high accuracy when calculating heat and moisture transfers in materials. Combining this method and the effective heat capacity method, a mathematical model was established for calculating heat and moisture transfer processes of PCHCM wallboards.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In this study, there were two aspects needed to be verified. Firstly, the humidity control process had already been verified as reliable in reference [41,42]. Then close humidity control function in the heat and moisture transfer model, considering phase change process only.…”
Section: Model Validationmentioning
confidence: 99%
“…Unfortunately, the application of thermal insulation materials resulted in substantial airtightness of buildings [2][3][4]. Besides the thermal performance of building envelopes, the moderation of the interior level of relative humidity became an important issue in order to achieve and preserve sufficient quality of indoor air [5].…”
Section: Introductionmentioning
confidence: 99%